Your patient safety survival guide : how to protect yourself and others from medical errors - Watson, Gretchen LeFever, 1960- (Rowman & Littlefield, 2017)
Medical errors happen all the time. Yet, it's not enough to rely on the health care system itself to remedy the problems. Patients must be aware of the risks and involved in the solutions. Here, the author looks at the most common risks, offers solutions patients can employ, and considers approaches to solving problems where they exist.